Targeting fibroblasts in pathological bone formation: mechanisms and treatments - Zhang, Qianyu; Song, Qimin; Li, Zeyin; Wu, Xinyi; Chen, Yuxiong; Lin, Hui (Frontiers in Cell and Developmental Biology, 2025)
Fibroblasts are integral to the pathological processes underlying abnormal bone formation, including heterotopic ossification (HO), ankylosing spondylitis (AS), and ossification of the posterior longitudinal ligament (OPLL). This review summarized the diverse roles of fibroblasts, from their transdifferentiation into osteoblast-like cells to their influence on inflammatory and mechanical signal transduction pathways, including those mediated by BMP, TGF-β, and Wnt/β-catenin. In particular, senescent fibroblasts can secrete Activin A to activate the BMP pathway to drive HO formation, and fibroblasts can also differentiate into osteoblasts via interactions among the TGF-β1, BMP-2, and FGF-2 pathways. In AS and OPLL, fibroblasts respond to inflammatory signals and mechanical stress, contributing to pathological bone formation through extracellular matrix remodeling and osteogenic gene expression. In rare cases, fibroblast-mediated abnormal ossification also occurs in diffuse idiopathic skeletal hyperostosis (DISH) and systemic sclerosis (SSc). Therapeutic strategies targeting fibroblast signaling pathways, inflammation, and senescence are highlighted as potential interventions to mitigate these conditions.